Changes in rate and socioeconomic inequality of cervical cancer screening in northeastern China from 2013 to 2018 - Liu, Yaqian; Guo, Jing; Zhu, Guangyu; Zhang, Bo; Feng, Xing Lin (Frontiers in Medicine, 2022)
Objective: Cervical cancer, the fourth leading cancer diagnosed in women, has brought great attention to cervical cancer screening to eliminate cervical cancer. In this study, we analyzed two waves of provincially representative data from northeastern China's National Health Services Survey (NHSS) in 2013 and 2018, to investigate the temporal changes and socioeconomic inequalities in the cervical cancer screening rate in northeastern China. Methods: Data from two waves (2013 and 2018) of the NHSS deployed in Jilin Province were analyzed. We included women aged 15–64 years old and considered the occurrence of any cervical screening in the past 12 months to measure the cervical cancer screening rate in correlation with the annual per-capita household income, educational attainment, health insurance, and other socioeconomic characteristics. Results: A total of 11,616 women aged 15–64 years were eligible for inclusion. Among all participants, 7,069 participants (61.11%) were from rural areas. The rate of cervical cancer screening increased from 2013 to 2018 (odds ratio [OR]: 1.06; 95% confidence interval [CI]: 1.04–1.09, p < 0.001). In total, the cervical cancer screening rate was higher among participants who lived in urban areas than rural areas (OR: 1.20; 95% CI: 1.03–1.39, p = 0.020). The rate was also higher among those with the highest household income per capita (OR: 1.30; 95% CI: 1.07–1.56, P = 0.007), with higher educational attainment (p < 0.001), and with health insurance (p < 0.05), respectively. The rate of cervical cancer screening was also significantly associated with parity (OR: 1.62; 95% CI: 1.23–2.41, p = 0.001) and marital status (OR: 1.45; 95% CI: 1.15–1.81, p = 0.001) but not ethnicity (OR: 1.41; 95% CI: 0.95–1.36, p = 0.164). Conclusion: Cervical cancer screening coverage improved from 2013 to 2018 in northeastern China but remains far below the target 70% screening rate proposed by the World Health Organization. Although rural-urban inequality disappeared over time, other socioeconomic inequalities remained.